2019
DOI: 10.31899/rh11.1021
|View full text |Cite
|
Sign up to set email alerts
|

No to circumcision: The road to effective social marketing campaigns in Egypt

Abstract: The Population Council confronts critical health and development issues-from stopping the spread of HIV to improving reproductive health and ensuring that young people lead full and productive lives. Through biomedical, social science, and public health research in 50 countries, we work with our partners to deliver solutions that lead to more effective policies, programmes, and technologies that improve lives around the world. Established in 1952 and headquartered in New York, the Council is a nongovernmental,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…There are multiple innovative and promising approaches being implemented in high prevalence countries, and evaluations have shown evidence on changes in intermediate outcomes such as changes in attitudes and reduced support for FGM; improved knowledge about the practice, its harms and its illegality; and intentions to perform FGM. For example, community engagement through information sessions on health, rights and female empowerment,115–117 school-based education118 and health education within health facilities119 as well as communications campaigns using social marketing and other communications approaches120–124 show promising results on intermediate outcomes such as knowledge, intentions to cut and reduction in attitudes supportive of FGM. In addition, investing in education of girls and women appears to be associated with decreased support for FGM, and women with higher levels of education were less likely to have their daughters undergo FGM 125–127.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple innovative and promising approaches being implemented in high prevalence countries, and evaluations have shown evidence on changes in intermediate outcomes such as changes in attitudes and reduced support for FGM; improved knowledge about the practice, its harms and its illegality; and intentions to perform FGM. For example, community engagement through information sessions on health, rights and female empowerment,115–117 school-based education118 and health education within health facilities119 as well as communications campaigns using social marketing and other communications approaches120–124 show promising results on intermediate outcomes such as knowledge, intentions to cut and reduction in attitudes supportive of FGM. In addition, investing in education of girls and women appears to be associated with decreased support for FGM, and women with higher levels of education were less likely to have their daughters undergo FGM 125–127.…”
Section: Discussionmentioning
confidence: 99%
“…Social marketing and media efforts. Research has shown that social marketing and media efforts are effective in changing social norms and attitudes towards abandoning FGM and in some cases, reducing the practice [11,26,36,50,83,[85][86][87][88][89][90][91][92][93][94]. Mainstream newspapers, television reports, SMS messaging, social media, theatre productions, television and radio melodramas can all shape conversations about FGM and accelerate the shift in social norms PLOS GLOBAL PUBLIC HEALTH towards FGM abandonment [26].…”
Section: Community Level: Addressing Gender Inequalities and Social N...mentioning
confidence: 99%
“…There also appears to be a substantially increased awareness not just of the illegality of FGM, but of the consequences of breaking the law [83] and of the negative impacts of infibulations [36]. Sensitization and training have also resulted in increased awareness and knowledge of the consequences and dangers of FGM, thereby contributing to disapproval and abandonment of the practice [11,26,85,88,92]. The UNFPA-UNICEF Joint Programme argues that young people can use social media to raise awareness about FGM and gender equality, as the promotion of FGM abandonment across social networks has given communities an opportunity to see the possibility of rapid, widespread change [95].…”
Section: Community Level: Addressing Gender Inequalities and Social N...mentioning
confidence: 99%